2005
DOI: 10.1002/hyp.6062
|View full text |Cite
|
Sign up to set email alerts
|

Rainfall interception by an isolated evergreen oak tree in a Mediterranean savannah

Abstract: Abstract:Redistribution of ground-level rainfall and interception loss by an isolated Quercus ilex tree were measured over 2 years in a Mediterranean oak savannah. Stemflow, meteorological variables and sap flow were also monitored. Rainfall at ground level was measured by a set of rain-gauges located in a radial layout centred on the tree trunk and extending beyond the crown limits. Interception loss was computed as the difference between the volume of rainwater that would reach the ground in the absence of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
105
2
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(116 citation statements)
references
References 27 publications
5
105
2
4
Order By: Relevance
“…Rainfall interception also differed depending on rainfall amount. Smaller (<10 mm) rainfall events experienced greater interception than larger ones, as observed in other systems (Llorens et al, 1997;David et al, 2006).…”
Section: Rainfall Redistribution Below the Hedgerowmentioning
confidence: 71%
“…Rainfall interception also differed depending on rainfall amount. Smaller (<10 mm) rainfall events experienced greater interception than larger ones, as observed in other systems (Llorens et al, 1997;David et al, 2006).…”
Section: Rainfall Redistribution Below the Hedgerowmentioning
confidence: 71%
“…Considering the projected shading by crown cover of the tree layer (minimum of 30 % at noon, increasing during the rest of the day; Piayda et al, 2015), the infiltration enhancement has potentially large benefits for the ecosystem level. A previous study of David et al (2006) under comparable climatic and stand density conditions estimated only minor interception losses of 8 % with respect to total canopy throughfall due to low canopy cover typical for cork oak systems. However, the integral balance of canopy interception losses, increased infiltration and other benefits of tree cover (compare Joffre andRambal, 1993, andDub-bert et al, 2014c) in this ecosystem could not be analysed in this study and need further investigations with regard to tree density and age.…”
Section: Infiltration and Distribution Of Event Watermentioning
confidence: 82%
“…Furthermore, widely space planted poplar may influence water relations more likely as individual trees. David et al (2006) estimated interception loss produced by an individual oak and showed that throughfall measurements in the windward side of the crown included wind-driven rainfall plus that dripping from the crown. The work of David et al (2006) could explain, in part, the spatial variability of soil moisture around the tree trunks shown in Fig.…”
Section: Discussionmentioning
confidence: 99%